(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: Work-related musculoskeletal disorders (WMSDs) are a major occupational health problem among farmers in Thailand. The purpose of this study was to evaluate the risk level and risk factors in work posture of durian farmers during pesticide spraying. Methods: This cross-sectional study was carried out among 82 durian farmers (n = 82) in southern peninsular Thailand. A questionnaire was used to collect data on socio-demographics and work characteristics. The posture analysis during pesticide spraying was done using Rapid Entire Body Assessment (REBA). The Chi-squared test was applied to find associations between socio-demographics or work characteristics with the risk level according to REBA assessments, with statistical significance requiring p<0.05. Results: REBA assessments indicated that most work postures during pesticide spraying by durian farmers had a high risk. Ergonomic risk factors for durian farmers involved prolonged work while standing in awkward postures, including bending the neck with more than 20° extension, bending the trunk with 0°-20° extension, raising and abducting the shoulder, both hands holding spray handles all the time, or carrying backpack pesticide sprayers with weights from 8 to 22 kg. Season, age, monthly income, pesticide spraying experience, pesticide spraying on other plants, pesticide spraying method, frequency of spraying pesticide, and durian tree height were statistically significantly associated with risk levels of work postures during pesticide spraying by durian farmers. Conclusion: Therefore, regular ergonomic training accompanied by modifications to the workstations and to tools for pesticide spraying are essential in improving work postures during pesticide spraying by durian farmers.